Penentuan Preservasi Jalan Nasional Berdasarkan Umur Sisa Perkerasan di Ruas Jalan Kaharudin Nasution – Marpoyan Kota Pekanbaru - Benny Hamdi Rhoma Putra; Yosi Alwinda; Muhammad Rilly Aka Yogi (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2022)
Jalan Kaharudin Nasution – Marpoyan has a length of 6.76 Km. This road has an important role in the process of moving human and goods traffic inside and outside the city of Pekanbaru. In maintaining the good condition of this road, goverment must do a road management program so that the road condition is always maintained. Knowing the current condition of the remaining structural life (RSL) of pavement can be used in preparing the types of road preservation works. This study uses data from the Riau Province National Road Implementation Center (BPJN) in the form of average daily traffic data (LHR) and deflection data. The results of the analysis showed that the condition of the Kaharudin Nasution-Marpoyan national road was 16.18% in good condition; 82.35% moderate condition; and 1.47% in a slightly damaged condition. While the road handling activities required are 41.17% of the length of the road requiring routine maintenance, and 58.82% of road segmen needs overlay.